The Influence of Green Product Innovation, Green Process Innovation, and End-of-Line Management Innovation on Sustainability Performance Dimensions - Masoudi, Ehsan; Emamiyan, Seyyed Amirhossein (SEISENSE Journal of Management, 2025)
Purpose- Sustainability performance (SP) boosts competitive advantage and benefits the environment and society. The present study analyzes the impact of green technology innovation (GTI) dimensions, namely green product innovation (GPtI), green process innovation (GPsI), and end-of-line innovation management (ELIM), on SP dimensions, namely economic performance (EcP), environmental performance (EnP), and social performance (SoP).Design/Methodology- A questionnaire instrument was developed and administered to a sample of 145 small and medium-sized enterprises (SMEs) located in the Tehran province of Iran. The data collected were analyzed using PLS-SEM.Findings- The data analysis results showed that GPtI and GPsI significantly influence EcP, EnP, and SoP. Furthermore, the findings indicate that while ELIM positively impacts EnP and SoP, it does not exert any influence on EcP.Practical Implications- This research highlights the significance of GTI in enhancing SP, providing practical implications for SMEs to adopt eco-friendly practices, thereby improving operational efficiency, reducing environmental impact, and fostering competitive advantage in the market.